Differential association of high-sensitive cardiac Troponin T and Troponin I with coronary atherosclerotic burden, inducible ischemia and long-term prognosis in patients with chronic coronary syndrome. (3rd October 2022) - Caselli, C; Ragusa, R; Prontera, C; Knuuti, J; Clerico, A; Neglia, D
Abstract: Background: High-sensitivity (hs) assays for the measurement of cardiac troponin T (cTnT) and cardiac troponin I (cTnI) are now used widely for the diagnosis of myocardial infarction. However, it is also increasingly apparent that troponin concentrations well below the thresholds used in acute coronary syndromes may provide diagnostic and prognostic information also for patients with chronic coronary syndromes (CCS). Purpose: This study is aimed at evaluating the association of hs-cTnT and hs-cTnI with clinical/molecular profiles, measures of myocardial ischemia and coronary artery disease (CAD), and their potential role as predictors of adverse cardiovascular events in a population of patients with CCS. Methods: Hs-cTnT and hs-cTnI were measured in 365 patients with CCS (mean age 61±8, 217 males) as part of the multicenter Evaluation of Integrated Cardiac Imaging (EVINCI) European study. Patients were characterized for clinical and molecular profile and underwent stress imaging to detect myocardial ischemia and coronary computed tomographic angiography (CTA) to assess the presence of CAD. An individual coronary CTA score was calculated combining extent, severity, composition, and location of plaques. All patients entered a clinical follow-up (1600±369 days). The composite cardiovascular outcome measure included all-cause mortality, non-fatal myocardial infarction, and hospitalization for unstable angina or heart failure. Clinical, molecular, and imaging parameters were used in a multivariate step-wise analysis to identify those associated with hs-cTnT and hs-cTnI. The possible role of troponins as independent predictors of adverse cardiovascular events was evaluated by Kaplan-Meier and Cox analysis. Results: The median values (IQR) of hs-cTnT and of hs-cTnI were 6.4 (4.9) ng/L and 4.4 (10.3) ng/L, respectively. In a multivariate model, age, gender, diabetes, NT-proBNP, and CTA score were independently associated with plasma hs-cTnT; triglycerides, HDL-cholesterol, and ischemia were independently associated with hs-cTnI (Table 1); interleukin-6 was associated with both troponins. At Kaplan-Meier analysis, event-free survival was significantly worse in patients with levels higher than the median values of both hs-cnT and hs-cTnI (Figure 1A, B). At Cox analysis, after correction for age, gender, and risk factors (EUROscore), only high hs-cTnI remained an independent predictor of cardiovascular events (hs-cTnT: HR 2.17, 95% CI, 0.87–5.41, P=ns; hs-cTnI: HR 2.65, 95% CI, 1.09–6.44, P=0.031). Conclusion: In patients with CCS, the presence and extent of coronary atherosclerosis is related with circulating levels of hs-cTnT, while the presence of ischemia is related with circulating levels of hs-cTnI, suggesting different mechanisms of release. Only high levels of hs-cTnI were independent predictors of cardiovascular events. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Grant from the European Union FP7-CPFP506-2007 (Evaluation ofIntegrated Cardiac Imaging for the Detection and Characterisation of Ischemic Heart Disease).